Baseline Vitamin D Levels Do Not Have Any Impact on Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis: A Retrospective Cohort Study - Adil Duman; Serdar Akca; Osman Cagin Buldukoglu; Besir Kaya; Galip Egemen Atar; Tolga Yalcinkaya; Ferda Akbay Harmandar; Serkan Ocal; Haldun Selcuk; Ayhan Hilmi Cekin (Diagnostic and Interventional Endoscopy)
Objective: Post-ERCP pancreatitis (PEP) is a recognized complication following endoscopic retrograde cholangiopancreatography (ERCP), with the inflammatory cascade playing a crucial role in the pathogenesis of PEP. Vitamin D, reported as a significant component of the immune system, influences inflammation and may correlate with acute pancreatitis. In this study, we aimed to investigate the role of vitamin D in the development of PEP.